Antibiotic Timing in Previable Prelabor Rupture of Membranes Less Than 24 Weeks of Gestation - Knupp, Rubymel J.; Pederson, Sarah; Blanchard, Christina; Szychowski, Jeff; Etikala, Deepa; Sinkey, Rachel; Wetta, Luisa; Harper, Lorie M. (American Journal of Perinatology, 2020)
Objective This study aimed to compare neonatal and maternal outcomes between immediate and delayed prophylactic antibiotic administration after previable prelabor premature rupture of membranes (PROM) less than 24 weeks of gestation.Study Design Retrospective cohort study of singleton pregnancies with PROM between 160/7 and 236/7 weeks of gestational age conducted at a single tertiary care referral center between June 2011 and December 2015. Patients with multiple gestations, fetal anomalies, those who elected augmentation, or with a contradiction to expectant management, such as suspected intra-amniotic infection or stillbirth, were excluded from the study. We compared pregnancy characteristics, maternal complications, and neonatal outcomes between women who received a course of antibiotics within 24 hours of PROM and women who received antibiotics after 24 hours of PROM. The primary outcome was neonatal survival to hospital discharge. Secondary outcomes included gestational age at delivery, time from PROM to delivery, neonatal birth weight, days in the neonatal intensive care unit (NICU), composite adverse neonatal outcomes, and maternal morbidity.Results Ninety-four women met inclusion criteria, 57 (61%) received antibiotics within 24 hours of PROM and 37 (39%) received antibiotics 24 hours after PROM. Baseline maternal characteristics were similar in both groups. The mean gestational age at PROM was similar between groups at 20.8 ± 2.3 weeks in the immediate antibiotics group and 20.6 ± 2.1 weeks in the delayed antibiotics group (p = 0.48). Compared with delayed antibiotic administration, immediate antibiotic administration was not associated with a significant difference in latency time from PROM to delivery, rate of stillbirth, days in an ICU, or adverse neonatal outcomes. Maternal outcomes also did not differ significantly between groups. Neonatal birth weight was lower in the immediate antibiotics group (p = 0.012).Conclusion Our data suggest that there is no maternal or neonatal benefit to immediate administration of latency antibiotics compared with delayed administration.Key Points
Keywords: previable; latency antibiotics; preterm; rupture of membranes